2021
DOI: 10.1177/08982643211027404
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Education for Middle- and Old-Age Mortality in Chile: Estimates From Panel Data Linked to Death Records

Abstract: Objectives To examine the association between education and mortality by age and gender in Chile. Methods We drew data from 10,147 adults aged 40 years and over from the Chilean Social Protection Survey linked to the national death records. We specify five Cox regression models to estimate the main and interaction effects for education levels, age, sex, and mortality. Results The hazard ratios reduce with increasing education. Secondary and tertiary education levels are associated, respectively, with 34% and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Our findings also suggest an inverse association between economic conditions (schooling level and occupation) and mortality for older ages. We found that older adults with higher education levels had a lower risk of mortality during follow-up than those with lower levels, corroborating with previous evidence from Chile 19,20 and other societies 21,22,23,24 . We also found that the type of living arrangement of older adults influences their longevity.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also suggest an inverse association between economic conditions (schooling level and occupation) and mortality for older ages. We found that older adults with higher education levels had a lower risk of mortality during follow-up than those with lower levels, corroborating with previous evidence from Chile 19,20 and other societies 21,22,23,24 . We also found that the type of living arrangement of older adults influences their longevity.…”
Section: Discussionsupporting
confidence: 91%
“…There are several factors that may explain these differences. A structural mechanism may be involved; in different societies (including Chile) low socioeconomic status is associated with worse health results and greater mortality ( 47 , 48 ). Table 1 indicates that Chilean Indigenous people have important socioeconomic disadvantages; for example, while the Chilean population has an average of 12.8 years of schooling ( 49 ), 27.7% of indigenous people have <8 years of schooling, which may result in poorer life conditions and greater exposition to diseases that affect their chances of survival.…”
Section: Discussionmentioning
confidence: 99%
“…G reater educational attainment is strongly associated with better health. Research has found this association across many world regions, 1–4 social contexts, 5–9 social groups, 10–13 and historical periods 14–19 . This association is not limited to one health outcome, but has been documented for an array of important measures, including self‐rated health, biological risk, chronic conditions, mental health, mortality, and physical and cognitive functioning 20–27 .…”
Section: Figurementioning
confidence: 90%